GE_GERICHTE A/309/2025 vom 9. September 2025 - GE Cour de justice (2025)
TAXI;RÉVOCATION(EN GÉNÉRAL);AUTORISATION D'EXPLOITER UN SERVICE DE TAXI;DROIT D'ÊTRE ENTENDU;POUVOIR D'APPRÉCIATION;PROPORTIONNALITÉ;LIBERTÉ ÉCONOMIQUE | Cst.27.al1; LTVTC.7.al3.lete; LTVTC.7.al5; RTVTC.6.al2; RTVTC.6.al3